Yield and Quality of Buffalo Milk in Semi-intensive and Intensive farming in Mymensingh District of Bangladesh (Research in Agriculture Livestock and Fisheries, 2025)
This study aimed to compare the buffalo milk yield and quality under semi-intensive and intensive management in village conditions. During the experiment, day-to-day milk production was recorded. pH, Acidity, Total solids, Specific gravity, Milk fat, Solids not fat, Lactose, Mineral, and standard plate count were evaluated. The average daily milk yield (L/d) of buffaloes under semi-intensive practice and intensive groups were 2.84 and 4.48 L/d, respectively, which were significantly different (p